2023
DOI: 10.1002/smll.202302465
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy: Molten Salt‐Assisted Synthesis to Enhance Lanthanide Upconversion Luminescence

Abstract: Lanthanide‐doped upconversion luminescent materials (LUCMs) have attracted much attention in diverse practical applications because of their superior features. However, the relatively weak luminescence intensity and low efficiency of LUCMs are the bottleneck problems that seriously limit their development. Unfortunately, most of the current major strategies of luminescence enhancement have some inherent shortcomings in their implementation. Here, a new and simple strategy of molten salt‐assisted synthesis is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Low doping can promote the nucleation and growth of particles to form larger particles whereas heavy doping can inhibit the nucleation and growth of particles and make the particle size smaller. 12,30–32 The high-resolution transmission electron microscope (HRTEM) image of the NaYbF 4 : 1 mol% Tm 3+ /10 mol% Fe 3+ (89Yb1Tm10Yb) sample (inset in Fig. 4h) reveals the single-crystalline attribute, as corroborated by the observed clear lattice fringes with a measured d -spacing of 0.296 nm, in good agreement with the lattice spacing in the (110) planes of h-NaYbF 4 (JCPDS no.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Low doping can promote the nucleation and growth of particles to form larger particles whereas heavy doping can inhibit the nucleation and growth of particles and make the particle size smaller. 12,30–32 The high-resolution transmission electron microscope (HRTEM) image of the NaYbF 4 : 1 mol% Tm 3+ /10 mol% Fe 3+ (89Yb1Tm10Yb) sample (inset in Fig. 4h) reveals the single-crystalline attribute, as corroborated by the observed clear lattice fringes with a measured d -spacing of 0.296 nm, in good agreement with the lattice spacing in the (110) planes of h-NaYbF 4 (JCPDS no.…”
Section: Resultssupporting
confidence: 63%
“…A great array of techniques have been developed to prepare various fluorides. 29–32 Unfortunately, the high-temperature solvothermal, hydrothermal and thermal decomposition methods broadly suffer from certain inherent handicaps of rigid synthesis conditions, exorbitant crude materials and the generation of substantial environmental loads, hindering their further large-scale industrial application, 29–32 which has stimulated continuous efforts towards finding facile large-scale techniques with simplicity, versatility, low cost, and environmental friendliness. Encouragingly, the low-temperature molten-salt (flux) technique has been shown to be an effective and convenient method for synthesizing fluoride micro-/nano-materials, including tetragonal (t-)LiYF 4 , 33 hexagonal (h)-NaYF 4 (ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 More importantly, the latest research demonstrated that the MSS method can enhance lanthanide upconversion luminescence in the Y 2 O 3 :Yb/Er system. 27 Unfortunately, there are few works about cubic ZrO phosphors synthesized by the MSS method and their upconversion (UC) luminescence. 28 In this work, a simple MSS method was proposed to synthesize rare earth-doped cubic ZrO 2 crystals using NaCl and KCl as the MS.…”
Section: Introductionmentioning
confidence: 99%
“…In general, owing to a very high melting point of 2715 °C, stabilized ZrO 2 is typically prepared through solid-state reaction at very high temperatures (>1400 °C). Meanwhile, it is widely known that the molten salt synthesis (MSS) method can be used to grow crystals at relatively low temperatures (much lower than those of the conventional solid-state reaction method) by using molten salts (MS) with a low melting point. , More importantly, the latest research demonstrated that the MSS method can enhance lanthanide upconversion luminescence in the Y 2 O 3 :Yb/Er system . Unfortunately, there are few works about cubic ZrO 2 phosphors synthesized by the MSS method and their upconversion (UC) luminescence .…”
Section: Introductionmentioning
confidence: 99%